2022
DOI: 10.3390/cancers14163915
|View full text |Cite
|
Sign up to set email alerts
|

FAM107A Inactivation Associated with Promoter Methylation Affects Prostate Cancer Progression through the FAK/PI3K/AKT Pathway

Abstract: Prostate cancer (PCa) is one of the most common cancers and is the second leading cause of mortality in men. Studies exploring novel therapeutic methods are urgently needed. FAM107A, a coding gene located in the short arm of chromosome3, is generally downregulated in PCa and is associated with a poor prognosis. However, the downregulation of FAM107A in PCa and the mechanism of its action remain challenging to determine. This investigation found that downregulation of FAM107A expression in PCa was caused by hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The FAK/PI3K/AKT signaling pathway is a pivotal player in cell proliferation, metastasis, and survival processes (Guo et al 2020 ; Ke et al 2022 ; Chen et al 2023 ; Ye et al 2023 ). Our findings indicate that flavokawain C is capable of downregulating the FAK/PI3K/AKT signaling pathway through the inhibition of FAK and PI3K phosphorylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The FAK/PI3K/AKT signaling pathway is a pivotal player in cell proliferation, metastasis, and survival processes (Guo et al 2020 ; Ke et al 2022 ; Chen et al 2023 ; Ye et al 2023 ). Our findings indicate that flavokawain C is capable of downregulating the FAK/PI3K/AKT signaling pathway through the inhibition of FAK and PI3K phosphorylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that YEATS2 was related to the PI3K/AKT signaling pathway and extracellular matrix (ECM). Activation of the PI3K/AKT pathway is associated with the malignancy of a variety of tumors, including gastric cancer, leukemia, prostate cancer, and breast cancer [ 27 , 28 , 29 , 30 ]. PI3K/AKT and downstream molecule mTOR can promote tumor proliferation, survival, metastasis, and invasion, and inhibit autophagy and senescence [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, activated FAK initiates survival pathways in a PI3K and MAPK-dependent manner. Simultaneously, within the nucleus, the FERM domain of FAK hinders the activation of p53, thereby preventing inherent cell apoptosis ( Del et al, 2022 ; Ke et al, 2022 ). Previous studies have delineated various mechanisms through which FAK promotes tumor cell survival and proliferation.…”
Section: Role Of Fak In the Occurrence And Development Of Tumorsmentioning
confidence: 99%